ANALISIS LAPORAN KEUANGAN UNTUK MENILAI KINERJA KEUANGAN PADA PT.AUSTINDO NUSANTARA JAYA,TBK YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE TAHUN 2013-2017 - Mastiur Sandora Manurung (Universitas Medan Area, 2020)
The purpose of this study is to assess the company's financial performance at PT.Austindo Nusantara Jaya, Tbk, which is listed on the Indonesia Stock Exchange with the use of financial ratio analysis for the period 2013-2017. Financial ratios used are Liquidity, Solvability, Activity, Profitability. This study aims to examine and analyze how the financial performance of PT.Austindo Nusantara Jaya, Tbk in 2013-2017 based on Analysis of Liquidity, Solvability, Activity, Profitability Ratios. This study was conducted at PT.Austindo Nusantara Jaya, Tbk, which was listed on the IDX. The object of this study consists of the Financial Position Report and the Comprehensive Income Statement 2013-2017. This research data was obtained through documentation techniques in the collection and recording of financial statements obtained from the Indonesia Stock Exchange (IDX) website, www.idx.co.id. The analysis method used is descriptive method.The results showed that 1) The financial performance of PT.Austindo Nusatara Jaya, Tbk in terms of Liquidity in the Current Ratio of 2013-2017 was 3.74, 1.22, 0.92, 1.43, 1.45 . Liquidityin the Quick Ratio is 3.20, 0.98, 0.76, 1.25, 1.31 that the condition of the liquid company. 2) Financial performance in terms of solvency in the debt ratio (Debt Ratio) of the results of 2013- 2017 amounting to 0.08, 0.15, 0.27, 0.32, 0.30 and Debt To Equity Ratio amounting to 0.03, 0.03, 0.21, 0.35, 0.30 that the condition of the company is good. 3) Financial performance in terms of activities in the ratio of Total Asset Turnover results in 2013-2017 amounted to 0.03, 0.34, 0.26, 0.25, 0.28. And Fixed Asset Turnover ratio is 1.52, 1.21, 0.77, 0.75, 0.92 that the condition of the company is good because it is able to make sales and earn profits. 4) Financial performance in terms of profitability at the ratio of gross profit margin in 2013-2017 of 0.24%, 0.22%, 0.04%, 0.14%, 0.45%, Net Profit Margin of 0.16%, 0.12%, 0.06%, 0.06%, 0.29% and Return On Equity at0.05%, 0.04%, 0.02%, 0.02%, 0.12% that the level of presentation the net profit obtained by the company is good.